(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The Never-Ending Museum of 1976 works like a guided tour of an imaginary museum. In this museum, there are works of art and critical reflection created by women in 1976, the year the artist was born. When talking about these works, sharing images and ideas, she reflects on the mentalities and affections that were on the agenda in the mid-1970s for women in different contexts. The artist’s natal chart gives the cards for the curatorship of this museum, bringing astrology to the scene as a creative lens, which offers an unusual imagery and narrative repertoire for approaching the arts, history and self-narratives.